Volatile secondary metabolites of Hypericum tetrapterum and Hypericum bithynicum. (December 2022) - Seyis, Fatih; Yurteri, Emine; Özcan, Aysel; Cirak, Cuneyt; Yayla, Fatih
Abstract: The phytochemical analyses on the flowering aerial parts resulted in identification of 32 and 30 compounds which represent 100% of total volatile components in Hypericum tetrapterum and Hypericum bithynicum (Hypericaceae), respectively. Among the chemicals, methylpalmitate, p- menthone, linalool and α-santalene for H. tetrapterum and camphor, α-bisabolol, methylpalmitate and nerolidol for H. bithynicum were recognized as major volatile ingredients. Volatile profile of H. tetrapterum from Turkish origin had never been described and this is the first report on volatile chemistry of H. bithynicum . Chemotaxonomic significance of the tested compounds was also discussed. Highlights: We describe volatile profile of Hypericum bithynicum for the first time. We also describe first volatile profile of Turkish Hypericum tetrapterum. Volatile profiles greatly varied with species. Results indicate no taxonomic value for volatile compounds. Results also indicate the possible pharmaceutical potential of both species.